An experimental study for quality assurance of free-form concrete panels produced by CNC machine - Lim, Jeeyoung; Kim, Do Yeong; Kim, Sunkuk (Journal of Civil Engineering and Management, 2018)
Various studies have been conducted to construct free-form buildings, but it still takes a lot of labor, cost, and time to assure the accuracy of designed shapes. In particular, molds for the production of free-form concrete panels (FCPs) are putting enormous burdens on productivity and cost. To produce FCPs economically, a computerized numeric control (CNC) machine that produces phase change material (PCM) molds for persistent use was developed in this study. The technology using CNC machine can produce precisely free-form molds and panels in a short time compared to the manual method. However, in order to commercialize this technology, it is necessary to verify the shape error of the FCPs. Therefore, the purpose of this paper is an experimental study for securing FCP quality produced by a CNC machine. The results of this study will be used to mass-produce uniform quality of FCPs without depending on the skill and workmanship of the labor.